PENINGKATAN KETERAMPILAN PRAKTIK INSTRUMEN PERKUSI MAHASISWA MELALUI PENGGUNAAN PORTOFOLIO - Herwin Yogo Wicaksono (FBS UNY, 2012)
This study aims to find out about (a) the use of portofolios in Percussion Music Instrument practical course, (b) to find out what can be done to improve students’ ability in learning to play this instrument. This research is an action research conducted in Music education Department, Yogyakarta State University. The subjects of this research are the students of semester I and semester III who take PIM Percussion course. The data were collected through a competence test, interviews, and observation. The data analysis technique was conducted by applying the quantitative descriptive analysis method which enables the researcher to present quantitative data, and qualitative descriptive method used to describe the data from observations and interviews. The research results show that through the use of portofolios, the students’ abilities to practice to play this instrument are significantly improved in terms of psychomotor, cognitive, and affective skills. This is proven with the average score gained by students of semester I, which is about 64.25 in Cycle I and 73.25 in Cycle II, and the average score gained by the students of Semester III, which is about 68 in Cycle I and 74.5 in Cycle II.